Enhanced thermal conductivity of polymer composites via hybrid fillers of anisotropic aluminum nitride whiskers and isotropic spheres. (1st April 2017) - Dang, Thi My Linh; Kim, Chang-Yeoul; Zhang, Yaming; Yang, Jian-Feng; Masaki, Takaki; Yoon, Dae-Ho
Abstract: Anisotropic aluminum nitride (AlN) whiskers and isotropic spheres were studied as hybrid fillers in epoxy and polyvinylidene fluoride (PVDF) matrices to enhance the thermal conductivity of polymer composites. Polymer composites with hybrid fillers in various volume ratios of AlN whiskers to spheres were prepared. The epoxy composite reached a maximum thermal conductivity of 4.321 (W/mK), obtained at the volume ratio of AlN whiskers to spheres of 1: 1 and the volume fraction of filler (Vf ) of 0.6. To improve the dispersion of the hybrid fillers within the polymer matrix and the interaction between hybrid fillers and polymer matrix, the surface of hybrid fillers was modified by silane couple agent. By loading the modified-hybrid fillers above the same filler content, the thermal conductivity of the epoxy composite increased significantly to 5.232 W/mK. This high thermal conductivity could be attributed to the formation of efficient three dimensional (3-D) heat conductive networks among the fillers.